Effect of 24 Hours of Normoglycaemia on Tissue-Type Plasminogen Activator Plasma Levels in Insulin Dependent Diabetes - Juhan-Vague, I; Vague, P; Poisson, C; Aillaud, M F; Mendez, C; Collen, D (Thrombosis and Haemostasis, 1984)
We have previously demonstrated that a short period of normoglycaemia obtained through an artificial pancreas in uncontrolled insulin-dependent diabetics improves parameters of the functional microangiopathy such as erythrocyte deformability and platelet aggregation. Because recently an immunoradiometric assay for tissue plasminogen activator (t-PA) was developed we measured t-PA levels in 18 uncontrolled insulin-dependent diabetics before and after 24 hr of normoglycaemia induced by insulin to look for a modification of endothelial cells function. After 24 hr of strict control, plasma free insulin levels rose significantly, total t-PA R-Ag, its active fibrin binding fraction and euglobulin fibrinolytic activity were significantly decreased. These results suggest a responsibility for insulin in the decrease in t-PA blood level and could explain at least partially the relation between hyperinsulinism, thrombosis and atherogenesis.
Keywords: Tissue type plasminogen activator; Insulin dependent diabetes; Artificial pancreas